A critical study to association between bleeding pattern and ultrasonographic findings in AUB patients in perimenopausal age in a tertiary care hospital - Devi, Jyoti; Singhal, Sunita; Sharma, Rupali; Saurabh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Abnormal uterine bleeding (AUB) is a prevalent gynecological condition, particularly among perimenopausal women, which significantly affects their quality of life. The International Federation of Gynaecology and Obstetrics (FIGO) introduced the PALM-COEIN classification to categorize the causes of AUB into structural and non-structural factors. Ultrasonography (USG), particularly transvaginal sonography (TVS), plays a pivotal role in diagnosing AUB by assessing endometrial thickness and identifying structural abnormalities like fibroids, adenomyosis, and endometrial polyps. However, the correlation between bleeding patterns and USG findings remains complex, and further research is necessary to improve diagnostic accuracy and management. Methods: This prospective observational study was conducted at GS Medical College and Hospital, Hapur, between November 2022 and February 2024. A total of 120 perimenopausal women, aged 40-50 years, presenting with various AUB patterns, were enrolled. Inclusion criteria included heavy menstrual bleeding, irregular cycles, intermenstrual bleeding, and continuous uterine bleeding. Exclusion criteria involved pregnancy, unstable hemodynamic, visible genital tract lesions, use of certain medications, and chronic systemic diseases. Data collection included clinical examinations, blood tests (haemoglobin, random blood sugar, thyroid-stimulating hormone), and transvaginal ultrasonography (TVS) for assessing uterine pathologies. Histopathological analysis was performed using endometrial biopsies. Data were analysed using SPSS version 26, with p-values <0.05 considered significant. Results: Among the 120 women, the most common bleeding pattern was menorrhagia (48.3%), followed by menometrorrhagia (19.2%), metrorrhagia (18.3%), and polymenorrhagia (14.2%). The ultrasonographic findings revealed fibroid uterus in 55.8% of cases, adenomyosis in 41.8%, endometrial polyps in 1.6%, and malignancy in 0.8%. There was a significant association between fibroid uterus and menorrhagia, and adenomyosis was more commonly found in polymenorrhagia cases. The cross-tabulation of bleeding patterns and USG findings demonstrated a strong correlation, particularly between fibroids and heavy menstrual bleeding. Conclusions: The study highlights a significant association between bleeding patterns and ultrasonographic findings in perimenopausal women with AUB. Menorrhagia was most commonly associated with fibroid uterus and adenomyosis. Transvaginal sonography plays a crucial role in identifying underlying structural uterine pathologies, facilitating accurate diagnosis, and enabling personalized treatment strategies. Future research should expand the sample size and incorporate advanced imaging techniques like MRI for comprehensive evaluation and better management of AUB in perimenopausal women.